The The Effect of Problem-Based Learning Assisted by Canva on Fifth Grade Students’ Conceptual Understanding in IPAS - Nurani Siparaga, Witri; Yusuf Ibrahim; Devi Rahmiati (Global Action and Education for Society, 2026)
This study aims to determine the effect of the Problem Based Learning model assisted by the Canva application on students' conceptual understanding of IPAS. The research method used is a quasi-experimental method with a Nonequivalent Control Group Design. Data analysis techniques include normality test, homogeneity test, hypothesis testing using the Paired Sample t-test, and effect size test with the assistance of IBM SPSS Statistics 29. The results of the Paired Sample t-test show a significance value (Sig. 2-tailed) of 0.001 < 0.05, indicating that H₀ is rejected and H₁ is accepted. Additionally, the effect size test shows a value of 1.288, which falls into the very large category. Therefore, it can be concluded that the Problem Based Learning model assisted by the Canva application has a significant effect on the conceptual understanding of IPAS among fifth-grade students at SDN 033 Asmi, Bandung City.